2010
DOI: 10.4314/naj.v40i1-2.55549
|View full text |Cite
|
Sign up to set email alerts
|

Growthand yield response of groundnut (<i>Arachis hypogaea</i> l.) to plant densities and phosphorus on an ultisol in southeastern Nigeria

Abstract: An experiment on the optimum planting density and Phosphorus requirement of a local Groundnut (Arachis hypogaea L.) cultivar, 'Graffi' was carried out at the Crop Science Research Farm of the University of Calabar, in the humid area of southeastern Nigeria, during the growing seasons of 2007 and 2008. Five Phosphorous rates 90, 20, 30, 40 and 50 kg P O /ha) were applied to five plant densities of Groundnut 2 5 (47619, 57128, 71428, 95238 and 142857 plants/ha) laid out in a RCB design in three replications. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 2 publications
3
11
1
1
Order By: Relevance
“…The maximum number of pods (39.28) and test weight (48.26 g) received the treatment T 8 -GNBJ-9M + 100% N followed by T 7 -GNBJ-9M + 75% N when compared to other treatments respectively in groundnut (Fig-3). The present findings are accordance with the results of Shiyam (2010).…”
Section: Number Of Pods Plant -1 and Test Weight (G) In Groundnutsupporting
confidence: 93%
See 1 more Smart Citation
“…The maximum number of pods (39.28) and test weight (48.26 g) received the treatment T 8 -GNBJ-9M + 100% N followed by T 7 -GNBJ-9M + 75% N when compared to other treatments respectively in groundnut (Fig-3). The present findings are accordance with the results of Shiyam (2010).…”
Section: Number Of Pods Plant -1 and Test Weight (G) In Groundnutsupporting
confidence: 93%
“…
ARTICLE INFO ABSTRACTGroundnut (Arachis hypogaea L.) is one of the most important oleaginous plants cultivated in globally and particularly in tropical and subtropical areas (Shiyam, 2010). This crop is commonly cultivated in arid and semi-arid regions of India where it plays an important socioeconomical role.
…”
mentioning
confidence: 99%
“…This suggested for a need of irradiation and a P application of 20 kg P 2 O 5 ha -1 for a good number of branches in the two (SAMNUT 24 and SAMNUT 26) genotypes. Shiyam (2010), in a study, reported a non-significant difference between P rates on plant height and numbers of flowers and branches. However, Gobarah et al (2006) reported an increase in vegetative growth due to increase in P rate of application.…”
Section: Effects Of Genotype and P Rate On Plant Height Numbers Of Bmentioning
confidence: 93%
“…It is an important cash crop for peasants in poor tropical countries [2]. Recently, this crop has been given great attention due to its suitability for growth in the newly reclaimed sandy areas in Egypt.…”
Section: Introductionmentioning
confidence: 99%